2004
DOI: 10.1007/s00213-004-1940-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of M1 muscarinic receptor agonism of N-desmethylclozapine in the unique clinical effects of clozapine

Abstract: The muscarinic receptor agonist activities of NDMC are unique among antipsychotics, and provide a possible molecular basis for the superior clinical effects of clozapine pharmacotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
164
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(171 citation statements)
references
References 46 publications
6
164
1
Order By: Relevance
“…In neuronal cells, ERK1/2 is known to participate in molecular pathways regulating learning, memory, and synaptic plasticity (Thomas and Hunganir, 2004). Previously, it has been reported that in mice the systemic administration of NDMC increased phospho-ERK1/2 immunoreactivity in the hippocampus and this response was blocked by pretreatment with scopolamine, indicating the participation of muscarinic receptors (Weiner et al, 2004). Studies in rats have shown that clozapine induced ERK1/2 phosphorylation in prefrontal cortex by blocking serotonin 5HT 2A receptors and that ERK1/2 inhibitors prevented clozapine suppression of the conditioned avoidance response, a behavioral index of antipsychotic activity (Browning et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In neuronal cells, ERK1/2 is known to participate in molecular pathways regulating learning, memory, and synaptic plasticity (Thomas and Hunganir, 2004). Previously, it has been reported that in mice the systemic administration of NDMC increased phospho-ERK1/2 immunoreactivity in the hippocampus and this response was blocked by pretreatment with scopolamine, indicating the participation of muscarinic receptors (Weiner et al, 2004). Studies in rats have shown that clozapine induced ERK1/2 phosphorylation in prefrontal cortex by blocking serotonin 5HT 2A receptors and that ERK1/2 inhibitors prevented clozapine suppression of the conditioned avoidance response, a behavioral index of antipsychotic activity (Browning et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Although these values do not allow the determination of the drug concentrations in the biophase, they are comparable with the potencies of NDMC in activating the d-opioid receptor in rat brain membranes. Moreover, whereas clozapine has higher affinity than NDMC at muscarinic M 1 and DA D 2 /D 3 receptors and potently antagonizes NDMC agonist activity at these receptors (Sur et al, 2003;Weiner et al, 2004;Burstein et al, 2005;Li et al, 2005), the affinity of clozapine for the d-opioid receptor is more than 10-fold lower than that of NDMC, suggesting that in the brain the demethylated metabolite could activate the receptors even in the presence of higher concentrations of the parent drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations